2011
DOI: 10.3109/10408444.2010.541900
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of dietary isoflavones for cancer

Abstract: A high intake of fruits and vegetables is associated with a lower risk of cancer. In this context, considerable attention is paid to Asian populations who consume high amounts of soy and soy-derived isoflavones, and have a lower risk for several cancer types such as breast and prostate cancers than populations in Western countries. Hence, interest focuses on soyfoods, soy products, and soy ingredients such as isoflavones with regard to their possible beneficial effects that were observed in numerous experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 565 publications
0
102
0
3
Order By: Relevance
“…The wealth of literature on the anticancer potential of isoflavones, contradictory and counterintuitive at times (99), highlights their enormous potential as nontoxic chemopreventive/therapeutic agents. Moving forward, it seems the best strategy might be to investigate a mixture of these compounds, as opposed to single agents, in more detailed studies.…”
Section: Discussionmentioning
confidence: 99%
“…The wealth of literature on the anticancer potential of isoflavones, contradictory and counterintuitive at times (99), highlights their enormous potential as nontoxic chemopreventive/therapeutic agents. Moving forward, it seems the best strategy might be to investigate a mixture of these compounds, as opposed to single agents, in more detailed studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Chinese study reported an inverse association between soy food intake and total mortality or cancer occurrence among breast cancer survivors, with a daily isoflavone intake of 62.7 mg and more, regardless of ER status in the breast cancers or tamoxifen use (Shu et al, 2009). Even though these studies are somewhat reassuring, experts believe that the literature is still missing data on the use of isolated isoflavones and supplements as well as the longterm safety of isoflavone supplements and soy extracts in breast tissue, especially among breast cancer patients and survivors (Andres et al, 2011).…”
Section: Phytoestrogensmentioning
confidence: 99%
“…Intentional dietary enrichment or supplement use is common in women seeking an alternative to hormonal replacement therapy and a preventive agent against breast cancer, osteoporosis, or cardiovascular disease [11][12][13] . More than 50% of breast cancer survivors use alternative medicine for hormone replacement therapy [14] , and isoflavones are one of their favorable choices [11,15,16] . On the other hand, the interactive effect of soy components and TAM on breast cancer was not well defined experimentally, and the results have been conflicting [17,18] .…”
Section: P E E R R E V I E W Abstract Abstractmentioning
confidence: 99%